PAX 8 positive synovial sarcoma - Miriam Fewtrell; Patricia Symons; Angela M. Hong; Peter Luk; Roland Jiang (Elsevier, 2021)
In this report, we describe a case of a biphasic tumour which presented as an incidental lump on the wrist of a 78 year old female. The epithelioid component predominated and was strikingly "gland-like", and in an elderly female raised concerns of a primary soft tissue tumour as well as a metastatic mixed Müllerian tumour. The unusual "gland" lining cells and odd central secretion did not fit classical glands and raised our suspicions of synovial sarcoma. We employed a panel of immunoperoxidase stains to consider synovial sarcoma as well as metastases, and included PAX8, ER and PR for possible gynaecologic and breast malignancies. Paired Box (PAX) 8 is a tissue-specific transcription factor protein, and immunohistochemical stains using antibodies raised against PAX 8 are frequently used in staining panels to help identify the origin of primary or metastatic malignancies, and in particular where tumours from the female genital tract, kidney, thyroid and thymus are included in the differential diagnosis. Our research into PAX8 revealed that it has been little studied in soft tissue sarcomas and there is limited published data in the English language literature regarding PAX8 staining particularly in primary extremity soft tissue synovial sarcomas. Unexpectedly, our panel of immunohistochemical stains showed PAX8 positivity for both the epithelioid and spindle cell components of our case, and again raised concerns of a gynaecological malignancy. The components showed differential PAX8 staining patterns, which is of note, and highlights the possible variability in staining of synovial sarcoma. Definitive diagnosis of biphasic synovial sarcoma was confirmed by fluorescent in situ hybridisation studies. This case report therefore documents PAX8 positive staining in biphasic primary soft tissue synovial sarcoma, demonstrating important considerations in its use, enabling the diagnosis of this infrequent and potentially aggressive soft tissue tumour. The relevant literature is highlighted. The variable range of appearances of this potentially aggressive tumour is further illustrated by our case which showed striking epithelial-rich morphology, and presented important diagnostic considerations. Careful morphologic examination together with immunohistochemical and molecular studies in our case enabled a definitive diagnosis of this histologically striking variant, with unexpected PAX8 positive staining.